2022
DOI: 10.1371/journal.pone.0269916
|View full text |Cite
|
Sign up to set email alerts
|

Impact of universal varicella vaccination on the use and cost of antibiotics and antivirals for varicella management in the United States

Abstract: Background Our objective was to estimate the impact of universal varicella vaccination (UVV) on the use and costs of antibiotics and antivirals for the management of varicella among children in the United States (US). Methods A decision tree model of varicella vaccination, infections and treatment decisions was developed. Results were extrapolated to the 2017 population of 73.5 million US children. Model parameters were populated from published sources. Treatment decisions were derived from a survey of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This data is even more interesting when considered on a large scale. Scenario analyses comparing no vaccination versus universal vaccination, showed that higher vaccination coverage was also cost saving, reducing annual expenditures for antibiotics in the United States from $82 million to $17 million [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data is even more interesting when considered on a large scale. Scenario analyses comparing no vaccination versus universal vaccination, showed that higher vaccination coverage was also cost saving, reducing annual expenditures for antibiotics in the United States from $82 million to $17 million [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Universal varicella vaccination is currently recommended in 12 European countries and mandatory only in Italy, Hungary and Latvia [ 12 ]. The impact of vaccination not only guarantees a protection from the viral disease, but is also associated with reduction in the use of antibiotics, in the costs for varicella management and in the spread of antimicrobial resistance [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, implementing universal varicella vaccination in the United States has significantly reduced the annual use of antibiotics and antivirals and their associated costs for children. 6 In China, VarV was first used in 1998, and the current vaccination procedure is to administer one dose of VarV to children above 12 months. 7 However, the varicella vaccine is still self-financed in China.…”
Section: Introductionmentioning
confidence: 99%
“…Varicella vaccine (VarV) is the most effective and economical measure to prevent and control the occurrence of varicella epidemics 5 . Moreover, implementing universal varicella vaccination in the United States has significantly reduced the annual use of antibiotics and antivirals and their associated costs for children 6 . In China, VarV was first used in 1998, and the current vaccination procedure is to administer one dose of VarV to children above 12 months 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of universal varicella vaccination on the use and cost of antibiotics and antivirals for varicella management has been evaluated in the USA pointing out that high vaccination coverage rates would imply a significant reduction in annual antibiotic and antiviral use. 49 …”
Section: Introductionmentioning
confidence: 99%